Factors influencing health-related quality of life among people with uncontrolled type II diabetes mellitus in Wenzhou, China: A cross-sectional study - Li, Huiwei; Moungkum, Saifone; Jullamate, Pornchai (Belitung Nursing Journal, 2025)
Background: China has a high prevalence of Type 2 Diabetes Mellitus (T2DM), and more than half of the population has uncontrolled blood sugar levels. As a result, this leads to a reduction in health-related quality of life (HRQOL). Therefore, identifying the factors that influence HRQOL in individuals with uncontrolled T2DM is a clinical priority. Objectives: This study aimed to describe the level of HRQOL among people with uncontrolled T2DM in Wenzhou, China, and to examine the predictive factors, including social support, diabetes distress, self-efficacy, and health literacy, in relation to HRQOL among these individuals. Methods: This predictive correlational study used a simple random sampling technique to recruit 107 adults with uncontrolled T2DM from the Endocrinology outpatient department at the First Affiliated Hospital of Wenzhou Medical University in Wenzhou, China, between August and September 2024. Data were collected through questionnaires and standardized tools to assess the correlation between HRQOL, social support, health literacy, self-efficacy, and diabetes distress. Data were analyzed using descriptive statistics and multiple regression analysis. Results: The HRQOL in this study was moderate (Mean = 3.34, SD = 0.31). Significant factors associated with HRQOL were health literacy (r = 0.819, p <0.01), self-efficacy (r = 0.825, p <0.01), and social support (r = 0.477, p <0.01). All predictor variables in the regression model collectively explained 79.8% of the variance in HRQOL among individuals with uncontrolled T2DM. Furthermore, health literacy (β = 0.426, p <0.001), self-efficacy (β = 0.463, p <0.001), and social support (β = 0.130, p = 0.009) were significant predictors of HRQOL. Conclusion: Enhancing health literacy, self-efficacy, and social support is crucial for improving HRQOL. Healthcare professionals and nurses should develop and implement intervention programs that help individuals and families enhance their critical thinking abilities and adopt lifestyles that support disease management and improve HRQOL.